2022
DOI: 10.3390/ph15080913
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Putative Dual Inhibitor of Tubulin and EGFR by Phenotypic Approach on LASSBio-1586 Homologs

Abstract: Combretastatin A-4 (CA-4, 1) is an antimicrotubule agent used as a prototype for the design of several synthetic analogues with anti-tubulin activity, such as LASSBio-1586 (2). A series of branched and unbranched homologs of the lead-compound 2, and vinyl, ethinyl and benzyl analogues, were designed and synthesized. A comparison between the cytotoxic effect of these homologs and 2 on different human tumor cell lines was performed from a cell viability study using MTT with 48 h and 72 h incubations. In general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In a previous study, LASSBio-1920 showed potent cytotoxicity and a better cytotoxic selectivity index against HL-60 cells [10][11][12]. In another study, the compound LASSBio-1586, in turn, stood out for exhibiting high cytotoxic effects against several cancer cell lines at nanomolar values (with MDA-MB435 showing the lowest IC 50 value, i.e., 64 nM), as well as the high cytotoxic selectivity index and microtubule polymerization inhibitory activity [28,29].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a previous study, LASSBio-1920 showed potent cytotoxicity and a better cytotoxic selectivity index against HL-60 cells [10][11][12]. In another study, the compound LASSBio-1586, in turn, stood out for exhibiting high cytotoxic effects against several cancer cell lines at nanomolar values (with MDA-MB435 showing the lowest IC 50 value, i.e., 64 nM), as well as the high cytotoxic selectivity index and microtubule polymerization inhibitory activity [28,29].…”
Section: Discussionmentioning
confidence: 95%
“…The study describes an N-acylhydrazone derivative of LASSBio-1586 [9], named LASSBio-1920, with potent in vitro cytotoxic activity, especially against HCT-116 cells (human colon cancer) and PC-9 cells (human lung cancer with overexpression of EGFR with L858R mutation). The study was based on QSAR (quantitative relationships between structure and activity), on in vitro analyses, and on molecular anchoring studies for the synthesis of the LASSBio-1920 analogue [10][11][12]. For that matter, molecular modeling for rEGFR in silico studies and the analysis of preliminary pharmacokinetic parameters to increase bioavailability were also carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homologation [ 9 ] studies on the amide nitrogen led to the benzyl homolog of LASSBio-1586 ( 54 ), LASSBio-2070 ( 56 ), which showed microtubule-stabilizing behavior, while the methylated homolog, LASSBio-1735 ( 55 ), had microtubule-destabilizing behavior. In addition, none of the compounds had better cytotoxic activity when compared to the N -methylated compound LASSBio-1735 ( 55 ) [ 46 ].…”
Section: The Methylation Effect In Pharmacodynamic Optimizationmentioning
confidence: 99%
“…Barbosa and colleagues [46] described a series of combretastatin A-4 analogs based on the N-acylhydrazone (NAH) LASSBio-1586 (54) with cytotoxic and antimitotic activity (Figure 14). Homologation [9] studies on the amide nitrogen led to the benzyl homolog of LASSBio-1586 (54), LASSBio-2070 (56), which showed microtubule-stabilizing behavior, while the methylated homolog, LASSBio-1735 (55), had microtubule-destabilizing behavior.…”
Section: Putative Dual Inhibitor Of Tubulin and Egfr By Phenotypic Ap...mentioning
confidence: 99%